The influence of steel slag as alternative aggregate in permeable concrete pavement - A. A. G., Nadiatul Adilah; S. Y., Ayman Mohammed; Putra Jaya, Ramadhansyah; O., Rokiah; Mohd Rosli, Hainin (2019)
This study identifies the pervious concrete with a high direct runoff on the pavement incorporating steel slag. This study is progressing in two stages i.e. 1ststage is obtaining the best mix design by using cubic concrete samples with dimension of 100mm height based on 7 days compressive strength test. Indeed, different proportion of aggregate and ratio were tested in order to select the highest compressive strength which has reached 10.9 MPa in the first 7 days of curing. The cylindrical concrete sample with the dimension of 200 x 100 mm was used in the 2nd stage. In addition, steel slag was used in the 2nd stage besides the granite aggregate. In fact, three different percentages of steel slag are involved; 50% Steel Slag and 50% Granite; 30% Steel Slag and 70% Granite; and 70% Steel Slag and 30% Granite. Hydrologically, 13.8 mm/s is the highest Infiltration rate that pervious concrete has reached which has been recorded throughout permeability test. The rainfall intensity which plays an important role on the pavement was identified. Thus, intensity distribution frequency curve was developed using MSMA and compared within filtration rate results of pervious concrete. Mix design ten (M10) has the ability to perform efficiently during highest rainfall intensity meanwhile strength needed to be increased since 10.9 MPa in the first 7 days of curing is not sufficient.